Peer Assessment of Professionalism: A Five-Year Experience in Medical Clerkship - Kovach, Regina A. (Springer-Verlag, 2009)
INTRODUCTION: Faculty assessment of students’ professionalism is often based upon sporadic exposure to students. Peers are in a unique position to provide valid judgments of these behaviors. AIMS: (1) To learn if peer assessments of professional conduct correlate with traditional performance measures; (2) to determine if peer assessments of professionalism influence the designation of honors, and (3) to explore student and faculty opinions regarding peer assessment. SETTING: Internal Medicine Clerkship at Southern Illinois University. PROGRAM DESCRIPTION: Since 2001 anonymous student peer assessments of professionalism have been used in assigning clerkship grades. PROGRAM EVALUATION: Peer assessments of professionalism had weak, though significant, correlations with faculty ratings (r = 0.29), performance on the NBME subject test (r = 0.28), and performance on a cumulative performance assessment (r = 0.30), and did not change the total number of honors awarded. A majority of students (71%) felt comfortable evaluating their peers, and 77% would keep the peer evaluation procedure in place. A majority of faculty (83%) indicated that peer assessments added valuable information. DISCUSSION: Peer assessments of professional conduct have little correlation with other performance measures, are more likely to have a positive influence on final clerkship grades, and have little impact on awarding honors.